Compound-archery-bow nocking-point locus in the vertical plane - Park, J. L. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2010)
In general, the path taken by the nocking point of an archery bow in the vertical plane is not a straight line perpendicular to the rest position of the string; it may vary significantly from that. Any deviation from a straight line at a draw length around the full-draw position will potentially lead to significant inaccuracy if the draw length varies by small amounts from arrow to arrow. This can occur for a compound bow if the cams do not come to their full-draw position simultaneously.